A First Report on [18F]FPRGD2 PET/CT Imaging in Multiple Myeloma. (27th July 2017) - Withofs, Nadia; Cousin, François; De Prijck, Bernard; Bonnet, Christophe; Hustinx, Roland; Gambhir, Sanjiv S.; Beguin, Yves; Caers, Jo
Abstract : An observational study was set up to assess the feasibility of [ F 18 ] FPRGD 2 PET/CT for imaging patients with multiple myeloma (MM) and to compare its detection rate with low dose CT alone and combined [ F 18 ] NaF/[ F 18 ] FDG PET/CT images. Four patients (2 newly diagnosed patients and 2 with relapsed MM) were included and underwent whole-body PET/CT after injection of [ F 18 ] FPRGD 2 . The obtained images were compared with results of low dose CT and already available results of a combined [ F 18 ] NaF/[ F 18 ] FDG PET/CT. In total, 81 focal lesions (FLs) were detected with PET/CT and an underlying bone destruction or fracture was seen in 72 (89%) or 8 (10%) FLs, respectively. Fewer FLs (54%) were detected by [ F 18 ] FPRGD 2 PET/CT compared to low dose CT (98%) or [ F 18 ] NaF/[ F 18 ] FDG PET/CT (70%) and all FLs detected with [ F 18 ] FPRGD 2 PET were associated with an underlying bone lesion. In one newly diagnosed patient, more [ F 18 ] FPRGD 2 positive lesions were seen than [ F 18 ] NaF/[ F 18 ] FDG positive lesions. This study suggests that [ F 18 ] FPRGD 2 PET/CT might be less useful for the detection of myeloma lesions in patients with advanced disease as all FLs with [ F 18 ] FPRGD 2 uptake were already detected with CT alone.